Muzeum Zabawek i Zabawy - Kielce - Bąk, Aneta (Biuletyn Historii Wychowania, 2008)
The article presents a short history of the Museum of Toys and Play in Kielce since its establishment in 1979 until present times. Moreover, attempts have been taken to demonstrate how functioning of this institution changed over the years. It has been shown that - apart from the fundamental activity concerning: the acquisition, description and presentation of the exhibits - the Museum fulfils a number of other functions. Information has been revealed regarding the unique character and originality of the museum collections. The questions of collectorship, co-operation with Polish and foreign museums and scholarly institutions in Poland have been dealt with. A new image of the Museum of Toys and Play, which was created after moving the institution to the new building was noticed, as well as its development and a multi-faceted character. Also, it wasn’t left unnoticed that the museum occupies now an important place on the map of Kielce.